Helicopter view of postgraduate research supervision at school of education: A critical reflection - Ksaveria Tuukamuwo Hambabi; Rachel Ndinelao Shanyanana-Amaambo; Lukas Matati Josua (European Scientific Journal, ESJ, 2024)
The University of Namibia has been committed to ensuring quality, equitable and just education opportunities for all students. However, there have been criticisms regarding the duration, processes and quality of student supervision in postgraduate studies. Students who enrol for coursework complete it with success, yet when it comes to research there has been a slow progression to successful completion. Therefore, this paper explores the landscape of postgraduate research supervision to gain a reflective understanding of concepts and related constraints. It is hoped that the review of the literature on research student supervision may assist role players to understand the supervisory process and identify strategies to mitigate potential constraints, towards effective postgraduate research. We adopted Schön’s reflection-in-action approach to review the postgraduate policies, documents and practices in the School of Education at the University of Namibia. The preliminary findings revealed that the supervision of postgraduate research is cumbersome, the proposal approval process is bureaucratic and unclear to students, and supervisors are slow to provide feedback. These hindrances lead to a prolonged stay in the programmes, which puts financial strain on students and ultimately affects progress towards completing the degree.